Experimental determination of the effect of fire-extinguishing agents on a decrease in the temperature indicators of cylindrical lithium-ion batteries - Lazarenko, Oleksandr; Pazen, Oleg; Ferents, Nadiia; Adolf, Ivan; Parkhomenko, Volodymyr-Petro (Eastern-European Journal of Enterprise Technologies, 2025)
This study defines fire hazard parameters for the Panasonic NCR18650B (LiNi0.8Co0.15Al0.05O2) lithium-ion battery (LIB). The task to obtain high-quality fire extinguishing substances and materials to prevent the spread of combustion implies determining the appropriate data experimentally. In particular, establishing the thermophysical characteristics and time dependence of the change in temperature indicators for the Panasonic NCR18650B (LiNi0.8Co0.15Al0.05O2) LIB depending on different fire extinguishing substances is a relevant issue that is resolved in this work. Based on the results of experimental studies, it was determined that the time of occurrence of the critical temperature inside LIB ( 170°C) exposed to an external energy source ( 300°C) is 400 s. The effectiveness of the use of water and carbon dioxide (CO2) on the effectiveness of reducing (cooling) the temperature of the internal filling was experimentally established. Accordingly, the time for reducing the battery temperature to 20°C with water is 400 s; when using CO2, it is 280 s. The mathematical model reasonably describes the cooling process of the LIB internal filling and accordingly verifies the experimental results of the study. The proposed mathematical model makes it possible to predict the complete cooling of the LIB depending on the type of extinguishing agent and the initial temperature of the substance. Additionally, the LIB heat transfer coefficients α (W/m2·°C) exposed to the action of water and CO2 were established, which are 20 and 50, respectively. The results make it possible to devise effective fire extinguishing agents and an algorithm for their application, in particular, to set the parameters of the extinguishing time and the required volume of the extinguishing agent in accordance with the power and type of battery. Additionally, the mathematical model built can be used for other types of LIBs with already known thermophysical characteristics